Angiogenic Factors and Inflammatory Bowel Diseases - Zhiru Li; Li Zeng; Wei Huang; Xinxing Zhang; Li Zhang; Qin Xie (Biomedicines)
Inflammatory bowel disease (IBD), including Crohn’s disease and ulcerative colitis, is characterized by chronic intestinal inflammation and impaired epithelial barrier function. Emerging evidence highlights the critical role of vascular remodeling and angiogenesis in IBD pathogenesis. This review explores the intricate relationship between blood vessels and the intestinal epithelial barrier, emphasizing how aberrant vascularization contributes to barrier dysfunction and disease progression. In IBD, excessive angiogenesis is driven by hypoxia, immune cell infiltration, and pro-inflammatory cytokines, further perpetuating inflammation and tissue damage. Key angiogenic factors, such as vascular endothelial growth factor (VEGF), angiopoietins, and platelet-derived growth factor (PDGF), are upregulated in IBD, promoting pathological vessel formation. These newly formed vessels are often immature and hyperpermeable, exacerbating leukocyte recruitment and inflammatory responses. Given the pivotal role of angiogenesis in IBD, anti-angiogenic therapies have emerged as a potential therapeutic strategy. Preclinical and clinical studies targeting VEGF and other angiogenic pathways have shown promise in reducing inflammation and promoting mucosal healing. This review summarizes current knowledge on vascular–epithelial interactions in IBD, the mechanisms driving pathological angiogenesis, and the therapeutic potential of anti-angiogenic approaches, providing insights for future research and treatment development.